2018
DOI: 10.1093/jisesa/iey010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Expression of Vitellogenin and Vitellogenin Receptor of Thitarodes pui (Lepidoptera: Hepialidae), an Insect on the Tibetan Plateau

Abstract: Vitellogenin (Vg) and vitellogenin receptor (VgR) play important roles in the vitellogenesis of insects. In this study, we cloned and characterized the two corresponding genes (TpVg and TpVgR) in an economically important insect, Thitarodes pui (Lepidoptera: Hepialidae), from the Tibetan plateau. The full length of TpVg is 5566 bp with a 5373 bp open reading frame (ORF) encoding 1,790 amino acids. Sequence alignment revealed that TpVg has three conserved domains: a Vitellogenin_N domain, a DUF1943 domain, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
4
18
0
Order By: Relevance
“…We cloned and identified the ORF sequences of SfVg and SfVgR from S. furcifera and analyzed the molecular characteristics of these genes. As expected, the amino acid sequence of SfVg contains the LPD_N, VWD and DUF1943 domains, all of which are highly conserved in most insects (Tufail et al, 2010;Wu et al, 2018;Yao et al, 2018). The motifs GL/ICG, DGXR and K/RXXR/K are also regarded as conserved domains in insect Vg proteins (Sappington and Raikhel, 1998;Upadhyay et al, 2016) and we found a GLCG motif at the C-terminal of SfVg.…”
Section: Discussionsupporting
confidence: 85%
“…We cloned and identified the ORF sequences of SfVg and SfVgR from S. furcifera and analyzed the molecular characteristics of these genes. As expected, the amino acid sequence of SfVg contains the LPD_N, VWD and DUF1943 domains, all of which are highly conserved in most insects (Tufail et al, 2010;Wu et al, 2018;Yao et al, 2018). The motifs GL/ICG, DGXR and K/RXXR/K are also regarded as conserved domains in insect Vg proteins (Sappington and Raikhel, 1998;Upadhyay et al, 2016) and we found a GLCG motif at the C-terminal of SfVg.…”
Section: Discussionsupporting
confidence: 85%
“…While most insect VgRs usually have five LDLR A repeats in the first and eight in the second LBD domain (Cong et al, ; Lu et al, ; Sappington et al, ; Schonbaum, Lee, & Mahowald, ; Tufail & Takeda, ; ), only four and seven LDLR A repeats were identified in LBD1 and LBD2 of CsVgR, respectively. Similar results were also reported in other Lepidopteran orthologs including SlVgR in S. litura (Shu et al, ), HaVgR in H. armigera (Zhang et al, ), SeVgR in S. exigua (Zhao et al, ), and TpVgR in T. pui (Wu et al, ). The presence of only four LDLR A repeats in LBD1 resembled the domain organization of VgRs in Hymenopteran and tick VgRs (Chen et al, ; Guidugli‐Lazzarini et al, ; Mitchell et al, ; Mitchell, Sonenshine, & Perez de Leon, ).…”
Section: Discussionsupporting
confidence: 84%
“…The vitellogenin receptor (VgR) is responsible for the receptor‐mediated endocytosis of Vg during the egg formation of insects. Since the first molecular characterization of VgR in Locusta migratoria (Ferenz, ), VgRs have been cloned in several insects, including Aedes aegypti (Sappington, Kokoza, Cho, & Raikhel, ), Solenopsis invicta (Chen, Lewis, Keeley, & Pietrantonio, ), Periplaneta americana (Tufail & Takeda, ), Apis mellifera (Guidugli‐Lazzarini et al, ), Spodoptera litura (Shu et al, ), Nilaparvata lugens (Lu et al, ) , Bombyx mandarina (Qian et al, ), Bactrocera dorsalis (Cong et al, ) , Helicoverpa armigera (Zhang et al, ), Bemisia tabaci (Upadhyay, Singh, Dixit, Mendu, & Verma, ), Spodoptera exigua (Zhao et al, ), Tibetan plateau (Wu et al, ), Colaphellus bowringi (Liu et al, ). The silico analysis indicates that insect VgRs are members of the low‐density lipoprotein receptor (LDLR) family (Sappington & Raikhel, ), which contains five typical domains including a ligand‐binding domain (LBD) containing Class A cysteine‐rich repeats (LDLR A ), the epidermal growth factor (EGF) precursor homology domain comprising Class B cysteine‐rich repeats (LDLR B , EGF‐like repeats) and YWXD repeats, an O‐linked sugar domain, a transmembrane domain (TMD) and a cytoplasmic domain (Tufail & Takeda, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of LDLa repeats in Hymenoptera differ from that in other insects. For example, there are four and seven LDLa repeats in Lepidoptera [12,15], five and eight repeats in Diptera and Blattaria [45]. Additionally, BLVgR contains two EGF-like domains, both of which include a calcium-binding site similar to the VgRs of A. mellifera, S. invicta and D. melanogaster.…”
Section: Discussionmentioning
confidence: 99%
“…In 1986, the VgR protein from the oocytes of the locust Locusta migratoria was first identified and purified [11]. Since then, it has been identified in a variety of economic insects [12,13] and agricultural pests [14][15][16][17]. In 2004, the cloning of the first hymenopteran VgR cDNA from the imported fire ant Solenopsis invicta (SiVgR) was reported, and this VgR was upregulated by methoprene, a juvenile hormone (JH) analog [18].…”
Section: Introductionmentioning
confidence: 99%